A model for the onset of self-gravitation and star formation in molecular gas governed by galactic forces: I. Cloud-scale gas motions - Meidt, Sharon E.; Leroy, Adam K.; Rosolowsky, Erik; Kruijssen, Diederik; Schinnerer, Eva; Schruba, Andreas; Pety, Jerome; Blanc, Guillermo; Bigiel, Frank; Chevance, Mélanie; Hughes, Annie; Querejeta, Miguel; et al. (The astrophysical journal, 2018)
Modern extragalactic molecular gas surveys now reach the scales of star-forming giant molecular clouds (GMCs; 20-50 pc). Systematic variations in GMC properties with galaxy environment imply that clouds are not universally self-gravitating objects, decoupled from their surroundings. Here we re-examine the coupling of clouds to their environment and develop a model for 3D gas motions generated by forces arising with the galaxy gravitational potential defined by the background disk of stars and dark matter. We show that these motions can resemble or even exceed the motions needed to support gas against its own self-gravity throughout typical galactic disks. The importance of the galactic potential in spiral arms and galactic centers suggests that the response to self-gravity does not always dominate the motions of gas at GMC scales, with implications for observed gas kinematics, virial equilibrium, and cloud morphology. We describe how a uniform treatment of gas motions in the plane and in the vertical direction synthesizes the two main mechanisms proposed to regulate star formation: vertical pressure equilibrium and shear/Coriolis forces as parameterized by Toomre Q ≈ 1. As the modeled motions are coherent and continually driven by the external potential, they represent support for the gas that is distinct from that conventionally attributed to turbulence, which decays rapidly and thus requires maintenance, e.g., via feedback from star formation. Thus, our model suggests that the galaxy itself can impose an important limit on star formation, as we explore in a second paper in this series.